The Effect of Emotional Intelligence on Nurse’s Communication Skill - Lusia Henny Mariati; Yohanes Jakri; David Djerubu (STIKes Patria Husada Blitar, 2022)
Practical and good communication is the key to carrying out their roles and functions for nurses. An obstacle in communication is the emotional response on the part of nurses. This study aims to acknowledge the effect of nurses' emotional intelligence â€“ which comprises emotional awareness, emotional control, self-motivation, empathy, and social skills â€“ on their communication abilities. Nurses with high emotional intelligence will give meaning to interpersonal relationships by making people feel at ease. The research method used quantitative with a cross-sectional design. The respondent was 96 nurses selected with proportional stratified random sampling method. The data was collected through a questionnaire. The results of multivariate analysis using multiple linear regression analysis statistical tests, obtained the values of Ï = 0.001; R2 = 0.209. Based on statistical test values, it can be concluded that nurses' emotional intelligence â€“ comprising emotional awareness, emotional control, self-motivation, empathy, and social skills â€“ significantly influences the communication skills of nurses at Ruteng Regional General Hospital simultaneously. Having a higher level of emotional intelligence leads to better communication with patients and a better level of health quality. It is expected that leaders and managers of nursing organizations should develop educational programs aimed at increasing the competencies of nurses in emotion control and communication skills.